Reescrevendo novos horizontes e possibilidades para a educação infantil a partir do amar e brincar - Moura, Luciéli Sodre de (2020)
The study and perceptions that are presented is linked to the line of research Teaching, Knowledge and Professional Development, of the Federal University of Santa Maria (UFSM), whose main objective is to investigate the importance of love and play for the integral development of children in Early Childhood Education from the propositions of Humberto Maturana and Gerda Verden-Zöller. These authors point out that love is the emotion that constitutes the human being, experienced through the relationship of the baby with the maternal figure, being supported by trust, respecting and accepting the other as legitimate. Our society believes that we are rational beings, but what governs our actions are our emotions. In this way, the human being is prioritizing a future of personal and professional achievements, imposing this goal on our children since childhood, but these relationships are not derived from love. The child is born loving, has no evil or prejudice, this way of living should be perpetuated, and adults should learn to be human beings with them. Another focus of the work is play, in the same way that love is established by the mother-baby relationship, so that the adult figure must always be attentive and available to the needs of the same. This play should be free, spontaneous and in the present moment, if not experienced in this way is not to play. This is how the child discovers worlds, his body, his social environment, his identity. This magic of play in contemporaneity is being lost, children end up having numerous extracurricular activities, with the aim of in the future standing out from the others. In many schools this play has also been lost, there is no more free space for imagination and creativity, they are cemented and closed, there is no nature, land and air. Love and play are fundamentals of the human being, which are being forgotten, as Maturana and Verden-Zöller point out, and we need to recover their essence. Dialogging with teacher training, a methodology was sought that could articulate practice and theory with teachers of early childhood education. Three from public schools and one from private school, through their experiences in love and play. The resource used to gather the information was semi- structured interviews, recorded with the consent of the participants. The teachers understand the relevance of free and spontaneous play for the biopsychosocial development of the child. However, it is perceived that in schools the time of the real play is reduced, replacing it with a pedagogical play, with the objective of preparing the child for the future. Just like play, love is present in the daily lives of teachers, because it is in this relationship of legitimacy of the other as a singular being, that trust, respect and acceptance are established, as a being who brings with him his baggage of knowledge and stories. It is necessary to visualize education starting from love, play and coexistence, where the child has his space to express himself, be spontaneous, develop imagination and creativity, living the present and respecting the time of eachchild.